Abdominal surgical site infection incidence, risk factors, and antibiotic susceptibility at a university teaching hospital in western Uganda: A cross-sectional study - Ariho Samuel B.; Lule Herman; Agwu Ezera; Shaban Abdullah (Zambia, 2022)
Background: Surgical site infection (SSIs) is a global burden that contributes towards morbidity and mortality of patients undergoing abdominal surgeries. There is paucity of data on SSIs in resource constrained Uganda to guide antibiotic protocols.
This study aimed to determine the incidence of SSIs, risk factors, common causative bacteria and their susceptibility patterns amongst patients undergoing abdominal surgeries at Kampala International University Teaching Hospital (KIUTH), Uganda.
Methods: Cross-sectional observational cohort study involving culture and sensitivity of pus swabs from surgical sites of consented consecutive patients. Laboratory tests were performed at the United States Army Research Laboratory on Infectious Diseases (USAMRIID). Data was analysed using SPSS 20.0. Chi-square and binary logistic regression analyses were performed at 95% confidence interval, regarding p<0.05 as significant to determine risk factors for SSIs.
Results: Of the 138 patients, 17.4% (n=24) developed SSIs. The risk factors for SSIs were comorbidity with diabetes mellitus, cancer without enrolment for anti-cancer treatment, pre-operative white blood cell count >11.0×109 cells/L, and HB <14.0g/dL, American Society of Anesthesiologists (ASA) score ≥II, surgery involving entry into the peritoneum. The bacteria responsible for SSIs were P. aeruginosa followed by E. coli, S. aureus, Methicillin Resistant S. aureus, K. pneumoniae and Proteus species in that order. These isolates demonstrated multiple drug resistance to gentamycin, amoxicillin-clavulanic acid, ceftriaxone, and ciprofloxacin.
Conclusions: The prevalence of SSIs in the present study was higher than previously reported. P. aeruginosa, E. coli, S. aureus, MRSA, and K. pneumoniae were the leading cause of SSIs. These bacteria demonstrated multiple drug resistance.
Keywords: antibiotic resistance, surgical site infection, sepsis, risk-factors, Uganda